2018
DOI: 10.1016/j.dib.2018.05.050
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies data on anticancer activity of Caesalpinia sappan L. heartwood and leaf extracts on MCF7 and A549 cell lines

Abstract: This article contains data on in vitro cytotoxicity activity of chloroform, methanolic and water extracts of leaf and heartwood of Caesalpinia sappan L. a medicinal plant against Breast cancer (MCF-7) and Lung cancer (A-549) cells. This data shows that Brazilin A, a natural bioactive compound in heartwood of Caesalpinia sappan L.induced cell death in breast cancer (MCF-7) cells. The therapeutic property was further proved by docking the Brazilin A molecule against BCL-2 protein (an apoptotic inhibitor) using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Evidence has shown that brazilin exhibits multiple functions such as anti-inflammation activity, anti-platelet activity, anti-oxidative activities, preventing hepatotoxicity, and inducing immunological tolerance. 20,[46][47][48][49] It was reported that brazilin can be distributed in brain after intravenous administration of 50 mg/kg brazilin to rats, 50) which indicates that brazilin may act directly in brain by passing through the blood brain barrier. Since oxidative stress plays a crucial part in MDD, so we assumed that brazilin may have an antidepression effect by acting as an anti-oxidative factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that brazilin exhibits multiple functions such as anti-inflammation activity, anti-platelet activity, anti-oxidative activities, preventing hepatotoxicity, and inducing immunological tolerance. 20,[46][47][48][49] It was reported that brazilin can be distributed in brain after intravenous administration of 50 mg/kg brazilin to rats, 50) which indicates that brazilin may act directly in brain by passing through the blood brain barrier. Since oxidative stress plays a crucial part in MDD, so we assumed that brazilin may have an antidepression effect by acting as an anti-oxidative factor.…”
Section: Discussionmentioning
confidence: 99%
“…1A), is well known for the natural red color dye for staining and has anti-oxidative stress, anti-inflammatory, anti-platelet concentration, and anti-cancer effects. [18][19][20][21] Considering the relationship of inflammation, oxidative stress and depression, in the present study, we evaluated the potential neuroprotective effects of brazilin on H 2 O 2 -induced rat pheochromocytoma (PC12) cell injury and chronic mild stress (CMS) mice model.…”
Section: Introductionmentioning
confidence: 99%
“…Significant cytotoxic property was observed for both crude extracts and bioactive compound. Further molecular docking proved the effectiveness of Brazilin A in the reduction of Bcl-2 apoptotic inhibitor [54]. Saraca asoca (Caesalpiniaceae family) was reported cytotoxic against AGS cell lines (IC50 value: 20 μg/mL).…”
Section: Caesalpiniaceaementioning
confidence: 95%
“…Dried heartwood of sappan has long been used as herbal medicines as it contains many phytochemicals and bioactive compounds 1 5 . The biological abilities of the wood extract in terms of antiacne 6 , anti-bacterial 7 , 8 , anticancer 9 , antidiabetic 10 , antidiarrhea 11 , antiinflammatory 12 – 14 , antioxidant 15 and anti-photoaging 16 activities have been demonstrated by a number of researchers.…”
Section: Introductionmentioning
confidence: 99%